Immunoblotting and culture positive endocarditis. Issue 2 (February 1991) - Clark, I; Burnie, J P
Abstract : Serum samples from patients with endocarditis due to Streptococcus mutans, Streptococcus pneumoniae, Streptococcus agalactiae, Streptococcus lactis and a "nutritionally" variant streptococcus were immunoblotted against antigenic extracts from all five species. In S mutans endocarditis there was an endocarditis specific pattern of IgM against bands of 220, 200, and 190 kilodaltons. In S pneumoniae IgM against antibody of a molecular weight greater than 150 kilodaltons was specific to endocarditis. In S agalactiae IgM against bands at 82, 71, and 66-67 kilodaltons was endocarditis specific. In S lactis endocarditis specific IgM was present against antigenic bands at 105, 66, 61 and 58 kilodaltons. With the "nutritionally" variant streptococcus it was impossible to distinguish between cases of endocarditis and controls.